Emerging Role of CREB in Epithelial to Mesenchymal Plasticity of Pancreatic Cancer - Mehra, Siddharth; Singh, Samara; Nagathihalli, Nagaraj (Frontiers in Oncology, 2022)
Pancreatic ductal adenocarcinoma (PDAC) is an aggressive solid malignancy with a high rate of metastasis and therapeutic resistance as its major hallmarks. Although a defining mutational event in pancreatic cancer initiation is the presence of oncogenic KRAS, more advanced PDAC lesions accumulate additional genomic alterations, including loss of tumor suppressor gene TP53. Co-occurrence of mutant KRAS and TP53 in PDAC promotes hyperactivation of cancer cell signaling pathways driving epithelial to mesenchymal plasticity (EMP). The cellular process of EMP influences the biological behavior of cancer cells by increasing their migratory and invasive properties, thus promoting metastasis. Our previous work has demonstrated that oncogenic KRAS-mediated activation of cyclic AMP response element-binding protein 1 (CREB) is one of the critical drivers of PDAC aggressiveness. The therapeutic approach of targeting this key transcription factor attenuates tumor burden in genetically engineered mouse models (GEMMs) of this disease. Herein, we discuss the significant role of CREB in perpetuating disease aggressiveness and therapeutic resistance through the EMP process. Furthermore, this review updates the therapeutic implications of targeting CREB, highlighting the challenges and emerging approaches in PDAC.